Darwin's Origin of species a biography - Browne, Janet 1950- (Grove Press, 2006)
Darwin's foremost biographer, historian Janet Browne, delivers an accessible introduction to the book that permanently altered our understanding of what it is to be human. A sensation on its publication in 1859, The Origin of Species profoundly shocked Victorian readers by calling into question the belief in a Creator with its description of evolution through natural selection. And Darwin's seminal work is nearly as controversial today. In this study, Browne delves into the long genesis of Darwin's theories, from his readings as a university student and his five-year voyage on the Beagle, to his debates with contemporaries and experiments in his garden. She explores the shock to Darwin when he read of a competing scientist's similar discoveries, and the wide and immediate impact of Darwin's theories on the world, showing why The Origin of Species can fairly claim to be the greatest science book ever published.--Résumé de l'éditeur.
Includes bibliographical references and index
Keywords: Darwin, Charles / The origin of species; Darwin, Charles <1809-1882>; Darwin, Charles <1809-1882> / On the origin of species; Darwin, Charles -- 1809-1882; Darwin, Charles -- 1809-1882 -- On the origin of species; Darwin, Charles -- 1809-1882 -- On the origin of species by means of natural selection; Naturalistes - Angleterre - Biographies; Naturalistes - Grande-Bretagne - Angleterre (GB) - Biographies; Naturalists -- England -- Biography; Natürliche Auslese; Darwinismus; Evolutionstheorie; Artbildung; Biografie; Fiktionale Darstellung